Role of a Contactin multi‐molecular complex secreted by oligodendrocytes in nodal protein clustering in the CNS. Issue 12 (22nd July 2019) - Dubessy, Anne‐Laure; Mazuir, Elisa; Rappeneau, Quentin; Ou, Sokounthie; Abi Ghanem, Charly; Piquand, Kevin; Aigrot, Marie‐Stéphane; Thétiot, Melina; Desmazières, Anne; Chan, Eric; Fitzgibbon, Matt; Fleming, Mark; et al.
Abstract: The fast and reliable propagation of action potentials along myelinated fibers relies on the clustering of voltage‐gated sodium channels at nodes of Ranvier. Axo‐glial communication is required for assembly of nodal proteins in the central nervous system, yet the underlying mechanisms remain poorly understood. Oligodendrocytes are known to support node of Ranvier assembly through paranodal junction formation. In addition, the formation of early nodal protein clusters (or prenodes) along axons prior to myelination has been reported, and can be induced by oligodendrocyte conditioned medium (OCM). Our recent work on cultured hippocampal neurons showed that OCM‐induced prenodes are associated with an increased conduction velocity (Freeman et al., 2015). We here unravel the nature of the oligodendroglial secreted factors. Mass spectrometry analysis of OCM identified several candidate proteins (i.e., Contactin‐1, ChL1, NrCAM, Noelin2, RPTP/Phosphacan, and Tenascin‐R). We show that Contactin‐1 combined with RPTP/Phosphacan or Tenascin‐R induces clusters of nodal proteins along hippocampal GABAergic axons. Furthermore, Contactin‐1‐immunodepleted OCM or OCM from Cntn1 ‐null mice display significantly reduced clustering activity, that is restored by addition of soluble Contactin‐1. Altogether, our results identify Contactin‐1 secreted by oligodendrocytes as a novel factor that may influence early steps of nodal sodium channel cluster formation along specific axon populations. Main Points: Oligodendrocyte secreted factors induce prenode formation on hippocampal GABAergic axons. Proteomic analysis of OCM to select clustering candidates. Contactin‐1 in association with Tenascin‐R or Phosphacan is responsible for prenodal clustering.